MODERN PROBLEMS OF PHYSICAL EDUCATION AND SPORTS IN SCHOOLCHILDREN AND STUDENTS - Pardaev Bakhrom Pulatovich (Galaxy International Interdisciplinary Research Journal, 2023)
The article is devoted to identifying current problems of modern sports and the physical health of students and schoolchildren. It contains data on surveys, in percentage terms. This article reflects the causes and global nature of problems with sports among students. It dispels the myths that sports are not for everyone and is engaged in attracting the attention of adolescents and students to physical activity. The article also talks about the role of physical education for the younger generation.